Butyrylated starch intake can prevent red meat-induced O6-methyl-2-deoxyguanosine adducts in human rectal tissue: A randomised clinical trial - Le Leu, R.; Winter, J.; Christophersen, Claus; Young, G.; Humphreys, K.; Hu, Y.; Gratz, S.; Miller, R.; Topping, D.; Bird, A.; Conlon, M. (Cambridge University Press, 2015)
© The Authors 2015 This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence (http://creativecommons.org/licenses/by/3.0/), which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.. Epidemiological studies have identified increased colorectal cancer (CRC) risk with high red meat (HRM) intakes, whereas dietary fibre intake appears to be protective. In the present study, we examined whether a HRM diet increased rectal O6-methyl-2-deoxyguanosine (O6MeG) adduct levels in healthy human subjects, and whether butyrylated high-amylose maize starch (HAMSB) was protective. A group of twenty-three individuals consumed 300 g/d of cooked red meat without (HRM diet) or with 40 g/d of HAMSB (HRM+HAMSB diet) over 4-week periods separated by a 4-week washout in a randomised cross-over design. Stool and rectal biopsy samples were collected for biochemical, microbial and immunohistochemical analyses at baseline and at the end of each 4-week intervention period. The HRM diet increased rectal O6MeG adducts relative to its baseline by 21 % (P< 0·01), whereas the addition of HAMSB to the HRM diet prevented this increase. Epithelial proliferation increased with both the HRM (P< 0·001) and HRM+HAMSB (P< 0·05) diets when compared with their respective baseline levels, but was lower following the HRM+HAMSB diet compared with the HRM diet (P< 0·05). Relative to its baseline, the HRM+HAMSB diet increased the excretion of SCFA by over 20 % (P< 0·05) and increased the absolute abundances of the Clostridium coccoides group (P< 0·05), the Clostridium leptum group (P< 0·05), Lactobacillus spp. (P< 0·01), Parabacteroides distasonis (P< 0·001) and Ruminococcus bromii (P< 0·05), but lowered Ruminococcus torques (P< 0·05) and the proportions of Ruminococcus gnavus, Ruminococcus torques and Escherichia coli (P< 0·01). HRM consumption could increase the risk of CRC through increased formation of colorectal epithelial O6MeG adducts. HAMSB consumption prevented red meat-induced adduct formation, which may be associated with increased stool SCFA levels and/or changes in the microbiota composition.